Bimtek Sekolah Penerima Bantuan Peralatan TIK 2021 Serta Pelatihan dan Simulasi Proktor Sekolah Region Sorong - Marwondo Marwondo (Jurnal Bhakti Karya dan Inovatif, 2022)
Assistance ICT tools are tools provided by the government to schools to be put to good use in improving the quality and access of education. Technical guidance related to the function of receiving, checking, and utilizing equipment will be able to provide an understanding so that ICT aid equipment really has added value in technology-based learning. Providing the right material and supported by adequate supporting equipment will help participants in understanding. Chromebooks as a major ICT tool as a new technology must be explored properly in order to be well adapted by schools. Through the presentation of material as well as practices and simulations, it turns out that participants' understanding can be better